Soluble stroma‐related biomarkers of pancreatic cancer. Issue 8 (25th June 2018) - Resovi, Andrea; Bani, Maria Rosa; Porcu, Luca; Anastasia, Alessia; Minoli, Lucia; Allavena, Paola; Cappello, Paola; Novelli, Francesco; Scarpa, Aldo; Morandi, Eugenio; Falanga, Anna; Torri, Valter; et al.
Abstract: The clinical management of pancreatic ductal adenocarcinoma (PDAC) is hampered by the lack of reliable biomarkers. This study investigated the value of soluble stroma‐related molecules as PDAC biomarkers. In the first exploratory phase, 12 out of 38 molecules were associated with PDAC in a cohort of 25 PDAC patients and 16 healthy subjects. A second confirmatory phase on an independent cohort of 131 PDAC patients, 30 chronic pancreatitis patients, and 131 healthy subjects confirmed the PDAC association for MMP7, CCN2, IGFBP2, TSP2, sICAM1, TIMP1, and PLG. Multivariable logistic regression model identified biomarker panels discriminating respectively PDAC versus healthy subjects (MMP7 + CA19.9, AUC = 0.99, 99% CI = 0.98–1.00) (CCN2 + CA19.9, AUC = 0.96, 99% CI = 0.92–0.99) and PDAC versus chronic pancreatitis (CCN2 + PLG+FN+Col4 + CA19.9, AUC = 0.94, 99% CI = 0.88–0.99). Five molecules were associated with PanIN development in two GEM models of PDAC (PdxCre/LSL‐Kras G12D and PdxCre/LSL‐Kras G12D/+ /LSL‐Trp53 R172H/+ ), suggesting their potential for detecting early disease. These markers were also elevated in patient‐derived orthotopic PDAC xenografts and associated with response to chemotherapy. The identified stroma‐related soluble biomarkers represent potential tools for PDAC diagnosis and for monitoring treatment response of PDAC patients. Synopsis: Seven stroma‐related circulating biomarkers that discriminate between healthy subjects and pancreatic ductal adenocarcinoma (PDAC) in two different cohorts of patients have been identified and suggested as a potential diagnosis tool to monitor treatment efficacy in patients. Panels of biomarkers that improve the performance of CA19.9 in distinguishing i) PDAC from healthy subjects and ii) PDAC from chronic pancreatitis have been developed. Multivariable models confirmed their predictive accuracy at early stages of disease. The association of these biomarkers with the development of pre‐invasive disease in GEM models confirmed their potential to detect early stage lesions. The correlation of biomarker levels with tumor burden and drug response in patient‐derived PDAC xenograft models indicate their value to monitor treatment response and efficacy. Abstract : Seven stroma‐related circulating biomarkers that discriminate between healthy subjects and pancreatic ductal adenocarcinoma (PDAC) in two different cohorts of patients have been identified and suggested as a potential diagnosis tool to monitor treatment efficacy in patients.